"How do ethnic minority patients experience the intercultural care encounter in hospitals? a systematic review of qualitative research". Issue 1 (December 2017) - Degrie, Liesbet; Gastmans, Chris; Mahieu, Lieslot; Dierckx de Casterlé, Bernadette; Denier, Yvonne
Abstract Background In our globalizing world, caregivers are increasingly being confronted with the challenges of providing intercultural healthcare, trying to find a dignified answer to the vulnerable situation of ethnic minority patients. Until now, international literature lacks insight in the intercultural care process as experienced by the ethnic minority patients themselves. We aim to fill this gap by analysing qualitative literature on the intercultural care encounter in the hospital setting, as experienced by ethnic minority patients. Methods A systematic search was conducted for papers published between 2000 and 2015. Analysis and synthesis were guided by the critical interpretive synthesis approach. Results Fifty one articles were included. Four dimensions emerged, describing the intercultural care encounter as (1) a meeting of two different cultural contexts of care, (2) in a dynamic and circular process of (3) balancing between the two cultural contexts, which is (4) influenced by mediators as concepts of being human, communication, family members and the hospital's organizational culture. Conclusions This review provides in-depth insight in the dynamic process of establishing intercultural care relationships in the hospital. We call for a broader perspective towards cultural sensitive care in which patients are cared for in a holistic and dignity-enhancing way.